Pengaruh Temperatur Air Pendingin Terhadap Efisiensi Dan Kinerja Turbin Di Pembangkit Listrik Tenaga Panas Bumi Unit 2 Lahendong - Zevanya Daniela Talumesang; Armstrong Sompotan; Sixtus Iwan Umboh (Jurnal FisTa : Fisika dan Terapannya, 2022)
Cooling water has a role in the process of condensing steam from the turbine to the condenser. Cooling water has an effect on maintaining the vacuum pressure in the condenser, so that the steam going to the condenser is maximally condensed. This study aims to determine the effect of variations of the cooling water temperature on the efficiency and performance of the turbine.. The research begins by reviewing the turbine conditions and turbine specifications including the surrounding environment. The higher the cooling water temperature, the greater the efficiency achieved. When the cooling water temperature is 29.14℃ the turbine efficiency value is 72% with the turbine performance value achieved is 627.568 kJ/kg. When the cooling water temperature is 30.43℃ the turbine efficiency achieved is 80% with the performance value achieved is 570,994 kJ/kg. The results also show that the higher the cooling water temperature, the turbine performance value will decrease and vice versa if the cooling water temperature decreases, the turbine performance value will increase.